Assume that there exists a function $f:\mathbb{R}\to\mathbb{R}$ that is bijective and satisfies $$ f(x) + f^{-1}(x)=x $$ for all $x$. Here $f^{-1}$ is the inverse function. Show that $f$ is odd.

This was a brain-teaser given to me by a friend. Two other related questions are:

  1. Show that $f$ is discontinuous
  2. Give an example of such a function (if indeed one exists).

Edit: As an initial idea, maybe approaching the problem graphically would help? A function and its inverse are reflections of each other about $y=x$ on the $x$-$y$ plane. Does this lead to anywhere?

  • $\begingroup$ I assume the domain must be $\mathbb R$? $\endgroup$ – 5xum Aug 17 '15 at 12:53
  • $\begingroup$ Yes the function is from the Reals to the Reals.\ $\endgroup$ – Iconoclast Aug 17 '15 at 13:08
  • 5
    $\begingroup$ One can show that $f(0)=0$ as follows: Let $f(0)=a$, then $f(0)+f^{-1}(0)=0$ or that $f^{-1}(0)=-a$. Therefore, $f(-a)=0$ and $f(0)=a$. Now, $f(-a)+f^{-1}(-a)=-a$, but since $f(-a)=0$, $f^{-1}(-a)=-a$ or that $f(-a)=-a$ so $-a=0$. $\endgroup$ – Michael Burr Aug 17 '15 at 13:10

Here is finally a constructive example of a solution, continuous except on a countable set.

Let $\phi = \frac{1+\sqrt5}{2}$, and let $$f(x) = \begin{cases} 0 & \text{if }x = 0 \\ -\phi x & \text{if }|x| \in [\phi^{3k}, \phi^{3k+1}), k \in \mathbb Z \\ \phi x & \text{if } |x| \in [\phi^{3k+1}, \phi^{3k+2}), k \in \mathbb Z \\ \phi^{-2} x & \text{if } |x| \in [\phi^{3k+2}, \phi^{3k+3}), k \in \mathbb Z \\ \end{cases} $$

Then $f$ is a bijection, whose inverse is $$f^{-1}(x) = \begin{cases} 0 & \text{if }x = 0 \\ \phi^2 x & \text{if }|x| \in [\phi^{3k}, \phi^{3k+1}), k \in \mathbb Z \\ -\phi^{-1} x & \text{if } |x| \in [\phi^{3k+1}, \phi^{3k+2}), k \in \mathbb Z \\ \phi^{-1} x & \text{if } |x| \in [\phi^{3k+2}, \phi^{3k+3}), k \in \mathbb Z \\ \end{cases} $$ Checking each case shows that $f(x)+f^{-1}(x) = x$, as required.

Plot of f

  • 4
    $\begingroup$ What intuition did you follow to arrive at this result? $\endgroup$ – templatetypedef Aug 18 '15 at 2:26
  • 2
    $\begingroup$ @templatetypedef I tried to build the function on $[1, \lambda)$ by setting $f(x)=-\alpha x$. See my other answer to see why this leads to a cycle $\pm[1, \lambda) \to \pm[\alpha, \alpha\lambda) \to \pm[\alpha+1, (\alpha+1)\lambda)$. Letting $\alpha=\lambda$ and $\alpha^2=\alpha+1$ enables the three intervals to be contiguous. At this point we have built the bijection on $[1,\phi^3)$. We can restart from $\phi^3$ to build the bijection on $[\phi^3, \phi^6)$, and so on. $\endgroup$ – yoann Aug 18 '15 at 10:40
  • 2
    $\begingroup$ A "golden" idea.... $\endgroup$ – Piquito Aug 30 '15 at 11:56

By plugging in $x=f(y)$ we obtain: $$ f(f(y))=f(y)-y $$ Call this assertion $P(y)$ and let $f^{(n)}(x)=\underbrace{f(f(…f(x)...))}_{n \space times}$. Now we have: $$ P(f(x)): f^{(3)}(x)=f(f(x))-f(x)=f(x)-x-f(x)=-x \iff f^{(4)}(x)=f(-x) $$ But: $$ P\left(f(f(x))\right): f^{(4)}(x)=f^{(3)}(x)-f^{(2)}(x)=-x-(f(x)-x)=-f(x) $$ By combining these equations, we obtain $f(-x)=-f(x)$ and therefore, $f$ is odd.

  • 2
    $\begingroup$ Nicely done. but what about continuity and existence? $\endgroup$ – Iconoclast Aug 17 '15 at 13:30
  • $\begingroup$ Thank you. I'm working on it :) $\endgroup$ – Redundant Aunt Aug 17 '15 at 13:33
  • $\begingroup$ Have you finished it? $\endgroup$ – Cooperation Jan 18 at 17:44

Proof that the function is odd (if it exists):

Suppose that $f(b)=a$. Now, consider $$f(b)+f^{-1}(b)=b.$$ Then, $f^{-1}(b)=b-a$ or that $f(b-a)=b$. Now, consider $$f(b-a)+f^{-1}(b-a)=b-a.$$ By substitution, we have $b+f^{-1}(b-a)=b-a$ or that $f^{-1}(b-a)=-a$. Therefore, $f(-a)=b-a$. Now, consider $$ f(-a)+f^{-1}(-a)=-a. $$ By substitution, $b-a+f^{-1}(-a)=-a$ or that $f^{-1}(-a)=-b$. In other words, $f(-b)=-a$, so the function is odd.

  • $\begingroup$ Better than accepted answer. Did you use bijective anywhere? $\endgroup$ – BCLC Aug 18 '15 at 12:56
  • $\begingroup$ Btw what exactly are b and a? I suspect that that is where bijection is used $\endgroup$ – BCLC Aug 18 '15 at 12:58
  • 2
    $\begingroup$ I only used the bijection to get that $f^{-1}$ exists. In this answer, $a$ and $b$ are arbitrary (satisfying the condition that $f(b)=a$). (The accepted answer is quite clean and provides insight on how to solve other similar questions.) $\endgroup$ – Michael Burr Aug 18 '15 at 13:03
  • 1
    $\begingroup$ googles more on bijection Strange. It seems that the fact of declaring the existence of $f^{-1}$ should be sufficient to mean that the function is bijective. Anyway, you mean repeated compositioning can solve other similar questions? $\endgroup$ – BCLC Aug 18 '15 at 13:08

First, as others have noted, we must have $f(0) = 0$. Let us now "construct" such a function on $\mathbb R^{*}$ using the Axiom of Choice.

Using $f(x) = x - f^{-1}(x)$, it is easy to see that, if $A \in \mathbb R^{*}$ is such that $f(A) = B$, then the following cycle must occur: $$A \mapsto B \mapsto B - A \mapsto -A \mapsto -B\mapsto A-B \mapsto A$$ (Note that this proves that the function is odd.)

Therefore, an idea to construct such a function is for instance to set $B = -2A$, so that we have the following cycle: $$A \mapsto -2A \mapsto -3A \mapsto -A \mapsto 2A \mapsto 3A \mapsto A$$

If we could partition $\mathbb R^{*}$ into sets of the form $\{-3A,-2A,-A,A,2A,3A\}$, we could easily define the function on each of these sets using the cycle above.

To do so, we can use the Axiom of Choice and take the quotient of $\mathbb R^{*}$ by the equivalence relation $$A \equiv B \Leftrightarrow \exists (p,q) \in \mathbb Z^2, A = \pm 2^p 3^q B$$

The Axiom of Choice gives us a set $X$ such that $\mathbb R^{*} = \coprod_{A \in X} \bigcup_{(p,q)\in\mathbb Z^2}\{\pm2^p3^qA\}$.

Then, for each $A\in X$, we can construct $f$ on $E_A = \bigcup_{(p,q)\in\mathbb Z^2}\{\pm2^p3^qA\}$. Indeed, since $\mathbb Z^2$ is countable, we can order it and use induction to build our cycles. When considering the $n$-th element of $\mathbb Z^2$, either it does not appear in a cycle formed by one of the previous elements of $\mathbb Z^2$, in which case we build $f$ on the cycle formed by the current element; or it does, in which case we skip the element.

It is easy to check that the function built this way has the required properties.

Note that I have no idea if we can build such a function without using the Axiom of Choice, but I doubt so.

Edit: I finally found a constructive solution, see my other answer. (If it is inappropriate to double-post, I will merge both answers.)

  • $\begingroup$ could you kindly tell me what is $\mathbb R^{*}$? Sorry for the rather basic question. $\endgroup$ – Iconoclast Aug 17 '15 at 17:10
  • $\begingroup$ @Iconoclast Just a notation: $\mathbb R^{*} = \mathbb R \setminus \{0\}$ $\endgroup$ – yoann Aug 17 '15 at 17:12
  • 3
    $\begingroup$ In my opinion it's nice to have your two answers separate. $\endgroup$ – user21820 Aug 18 '15 at 17:16

If $f$ were continuous, then it would have to be strictly monotonic, since it's bijective. Suppose $f$ is decreasing, $x>0$. Then, since $f(0)=0$ we get $f(x)<0$ and $f^{-1}(x)<0$, but $x=f(x)+f^{-1}(x)$. So $f$ is increasing and $f(x)>0$ when $x>0$. But then, $f^{-1}(x)$ is also positive for $x>0$, so $f(x)<x$. Since $f$ is increasing, $f^{-1}(x)>x$. But that's not possible.

  • $\begingroup$ So does this mean that $f(x)$ is discontinuous everywhere? i.e., continuous on no internal? $\endgroup$ – Iconoclast Aug 17 '15 at 13:49
  • $\begingroup$ This only shows that it has a discontinuity. I suspect such a function ( if one exists ), is very discontinuous, but I'm still thinking about it. $\endgroup$ – Callus - Reinstate Monica Aug 17 '15 at 13:56

Let's call $(E)$ the equation $f(y) + f^{-1} (y) = y$

Let $a \in \mathbb{R}$. Since $f$ is bijective, there exists $x \in \mathbb{R}$ such that $f(x) = a$. Now, since $f^{-1}(a) = x$, we have (using $(E)$ with $y = a$) $f(a) = a - x$. Now, using $(E)$ with $y = x$:

$$f^{-1}(x) = x - a$$ Applying $f$ on both side: $$f(x-a) = x $$ Using $(E)$ with $y = x-a$: $$f^{-1}(x-a) = x - a - f(x -a) = x -a -x = a$$ Applying $f$ on both side: $$f (-a ) = x -a $$.

Thus $f(a) = a - x = -f(-a)$. This is true for all $a \in \mathbb{R}$: $f$ is therefore odd.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.